Psychophysics beyond sensation : laws and invariants of human cognition - Kaernbach, Christian; Schröger, Erich; Müller, Hermann (Mahwah, N.J. : Lawrence Erlbaum, 2004)
This volume presents a series of studies that expand laws, invariants, and principles of psychophysics beyond its classical domain of sensation. In spite of the equivalence of methods, such contributions are often not regarded as "psychophysics." In summary, this book explores psychophysical approaches to issues concerning internal representations, memory, and action, which consider general questions of the timing of brain dynamics and provide frameworks for context-dependent and multidimensional generalizations of psychophysical theory, in order to advance psychophysics as a seminal approach to psychological science and the understanding of the human mind. The book should be of great interest to advanced (postgraduate) students in neuroscience, cognitive science, psychology, neuropsychology, and related areas who seek to evaluate the range and power of psychophysical work today, and to established scientists in those fields who will appreciate the variety of issues addressed within the same methodological framework and their multiple interconnections and stimulating cross-talk.
Structural Information Theory and Visual Form / Emanuel Leeuwenberg
Bibliografija
Kazala